Care planning according to the international standard ICNP® in Primary Health Care — a case study of individual - Kilańska, Dorota; Staszewska, Milena; Urbanek, Natalia; Andrzejak, Aleksandra; Purgał, Justyna (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction to the practice of nursing reference terminology organizes and unifies that practice. It helps within the meaning of nursing diagnoses and interventions. The reference Terminology supports the work using of the nursing process. Implementation, in the process of nursing, the International Classification for Nursing Practice (ICNP) will help implement an electronic patient record (EHR) for nurses. Visibility the work of the nurses its importance for the therapeutic process, it is a milestone in the health system. For documenting nursing phenomena is also necessary to indicate the International Minimum Data Set for Nursing — INMS. This allows to analyze and evaluate the practice. Working by the nursing process in the Primary Health Care (PHC) is a challenge due to the nature of the practice. The time that nurses can spend with patients also allows the evaluation of the care plan. It is an essential part of preparing a patient for self-care capacity the family context in nursing care. Nursing Topics 2014; 22 (4): 539–545